Implementation of Human Rights and the Mandatory Precedents in Foreign Trade, Legal Effectiveness: Mexico Case - Ramirez, Laura Hernandez (Archives of Business Research, 2021)
We make an analysis of the implementation of human rights and the mandatory precedent in matters of Mexican foreign trade, in an administrative and judicial context in the search for legal effectiveness with constitutional control, highlighting the implementation of human rights contained in treaties commercial, such as access to justice and prompt and expeditious; We point out a recent case of human rights and foreign trade, with the implementation in the Mexican legal system, of the Free Trade Agreement Mexico United States Canada, before the Supreme Court of Justice of the Nation, as well as a possible proposal before the provisions of its Article 14.D.5, regarding the right of access to prompt and expeditious justice in investment matters, and avoiding the resolution of controversies before international arbitration panels that have been questioned.